Learning Obstacles Hindering Junior High School Students Understanding of Surface Area of a Prism - Siahaan, Erika Yohanna Seventina; Dasari, Dadan; Suryadi, Didi (FKIP Universitas Lampung, 2024)
Abstract: Learning Obstacles Hindering Junior High School Students Understanding of Surface Area of a Prism. Objectives: to reveal the learning obstacles experienced by students in learning the surface area of prisms. Methods: using a qualitative method with a phenomenological design on grade IX junior high school students in Bandung as many as 29 students. Data were analyzed with the stages of data reduction, data presentation, and conclusion drawing. Findings: The results showed that students did not understand the prerequisite materials needed to understand the concept of prism surface areas such as the area of flat buildings and the Pythagorean theorem. Teachers also do not familiarize students with practicing non-routine problems so as not to spur students to form their knowledge acquisition maximally. Conclusions: students experience learning obstacles that are ontogenic, didactic, and epistemological in solving mathematical problems regarding the concept of prism surface area. The implications of this research can be utilized by educators, prospective educators, or researchers in the future to provide solutions to student learning obstacles in understanding the concept of prism surface area. Keywords: concept of prism surface area, geometry, mathematics, learning obstacles.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202413